Colloidal Nanocrystals of Lithiated Group 14 Elements1. Issue 52 (3rd November 2014) - Cloud, Jacqueline E.; Wang, Yonglong; Yoder, Tara S.; Taylor, Lauren W.; Yang, Yongan
Abstract The synthesis of colloidal nanocrystals (NCs) of lithiated group 14 elements (Z=Si, Ge, and Sn) is reported, which are Li4.4Si, Li3.75Si, Li4.4Ge, and Li4.4Sn. LixZ compounds are highly reactive and cannot be synthesized by existing methods. The success relied on separating the surface protection from the crystal formation and using a unique passivating ligand. Bare LixZ crystals were first produced by milling elemental Li and Z in an argon‐filled jar. Then, under the assistance of additional milling, hexyllithium was added to passivate the freshly generated LixZ NCs. This ball‐milling‐assisted surface protection method may be generalized to similar systems, such as NaxZ and KxZ. Moreover, Li4.4Si and Li4.4Ge NCs were conformally encapsulated in carbon fibers, providing great opportunities for studying the potential of using LixZ to mitigate the volume‐fluctuation‐induced poor cyclability problem confronted by Z anodes in lithium‐ion batteries.